2011
DOI: 10.1055/s-0031-1280783
|View full text |Cite
|
Sign up to set email alerts
|

The Cholestyramine-induced Decrease of PYY Postprandial Response is Negatively Correlated with Fat Mass in Obese Women

Abstract: Obese patients have decreased fasting and postprandial levels of peptide YY (PYY), an anorexigenic peptide produced by the L cells of the gastrointestinal mucosa. Fatty nutrients are the most powerful stimulus for PYY release. Cholestyramine, an anion exchanger which adsorbs bile salts, reduces digestion of lipids. The aim of the present study was to investigate the effects of cholestyramine or placebo on PYY secretion in obese women administered a high-fat meal [n=8; age: 30.9±2.7 years; BMI: 47.3±3.3 kg/m2].… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 9 publications
0
12
1
Order By: Relevance
“…In addition, a negative correlation has been reported between circulating levels of these anorexigenic peptides and adiposity, evaluated as BMI and FM (26,27). In this study, despite a significant difference in BMI between the two groups, there was no correlation between postprandial responses in GLP1 and PYY and BMI or FM.…”
Section: Discussioncontrasting
confidence: 58%
“…In addition, a negative correlation has been reported between circulating levels of these anorexigenic peptides and adiposity, evaluated as BMI and FM (26,27). In this study, despite a significant difference in BMI between the two groups, there was no correlation between postprandial responses in GLP1 and PYY and BMI or FM.…”
Section: Discussioncontrasting
confidence: 58%
“…A previous study of our group showed a suppressant effect of cholestyramine on postprandial PYY secretion also in patients with simple obesity [27]. The mechanism by which cholestyramine reduces the plasma PYY response to the high-fat meal is presumably different from that responsible for the increase of postprandial CCK release.…”
Section: Discussionmentioning
confidence: 86%
“…The drug (3 packets, each containing 4 g of the drug) was dissolved in the same volume as the placebo. The dose of cholestyramine was chosen on the basis of a previous work of ours [27]. No significant difference emerged among subjects in the mean time required to consume the meal in the two tests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…I also have some comments about the study design and statistical analysis used by van Avesaat et al First, it may be possible that hormone release or hormone response on the receptor area is affected by fat mass (2). We know that fat mass in individuals with normal BMI may exceed the range that is usually classified as normalweight obesity or latent obesity.…”
mentioning
confidence: 99%